Structures and Elastic Properties of Crystalline and Amorphous $BC_2N$ Solids (Journal of Atomic and Molecular Sciences, 2010)
Crystalline and amorphous $BC_2N$ supercells with 216 atoms have been constructed by random distributions of $B,$ $C,$ and $N$ atoms in the diamond lattice and amorphous sp$^3$ carbon structure, respectively. The atomic structures of these two systems were relaxed using density functional theory, and their mechanical properties including the bulk modulus, shear modulus, and Young's modulus were computed. Crystalline $BC_2N$ possess higher elastic moduli than those of cubic $BN.$ Amorphous $BC_2N$ exhibit reasonable elastic moduli and appreciable ductility with a large ratio between the bulk modulus and shear modulus. Both crystalline and amorphous $BC_2N$ are superior candidates as superhard materials.
Keywords: $BC_2N; $ structure; elastic properties; superhard material.